Rethinking Regulations: Unlocking the Potential of Small-Scale Public-Private Partnerships in Infrastructure Development - Kurdi, Kurdi; Amalia, Prita; Wardhana, Yuki M.A (DiH: Jurnal Ilmu Hukum, 2025)
Implementation of infrastructure development often faces bureaucratic and funding challenges. To address these issues, the National Development Planning Agency (Bappenas) launched the Small-Scale Public-Private Partnership (PPP) scheme, as regulated by the Minister of National Development Planning/Bappenas Head Regulation No. 7 of 2023. This scheme aims to facilitate and accelerate infrastructure development in regions with limited budgets, such as the street lighting project in Madiun, which uses the Availability Payment scheme. This study employs a normative juridical method with a conceptual and legislative approach to analyze the renewal of regulations governing Small-Scale PPPs. The main focus is on the legal clarity and implementation of this scheme, which still requires refinement. Although the Small-Scale PPP has a legal basis, existing regulations need to be updated to address the various practical and bureaucratic obstacles. The study recommends strengthening the role of the central government in supporting the implementation of Small-Scale PPPs and revising Article 85 of the Minister of National Development Planning/Bappenas Head Regulation No. 7 of 2023 to ensure the effectiveness and efficiency of this scheme's implementation.